2015
DOI: 10.1002/phar.1550
|View full text |Cite
|
Sign up to set email alerts
|

Drug Reaction with Eosinophilia and Systemic Symptoms Syndrome Probably Induced by a Lamotrigine-Ginseng Drug Interaction

Abstract: The likelihood of a drug reaction with lamotrigine is increased by dose escalation that is too rapid or drug interactions that increase the concentration of lamotrigine. There is a well-documented interaction between valproic acid and lamotrigine in which lamotrigine levels are increased, subsequently increasing the risk of a drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome. This syndrome is characterized by fever, lymphadenopathy, diffuse maculopapular rash, multivisceral involvement, eo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Lamotrigine is an aromatic anticonvulsant drug that is hepatically eliminated through glucuronidation by the uridine diphosphate glucuronosyl transferase enzyme. 2 Valproate is a broad spectrum inhibitor of the uridine diphosphate glucuronosyl transferase enzyme. 3 When valproate is used in combination with lamotrigine, because of the inhibition of elimination, the half-life of lamotrigine prolongs and its serum levels elevate.…”
Section: Discussionmentioning
confidence: 99%
“…Lamotrigine is an aromatic anticonvulsant drug that is hepatically eliminated through glucuronidation by the uridine diphosphate glucuronosyl transferase enzyme. 2 Valproate is a broad spectrum inhibitor of the uridine diphosphate glucuronosyl transferase enzyme. 3 When valproate is used in combination with lamotrigine, because of the inhibition of elimination, the half-life of lamotrigine prolongs and its serum levels elevate.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that VA in co-administration with Lamotrigine (LMT) increases the risk of Lamotrigine-induced ADRs [7,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Over these studies, 32 aimed to highlight only PK mechanisms such as area under the curve, half-life, or clearance. Only five studies considered clinical effects rather than only PK parameters (CS 3,10,25,33,34) [46,49,55,61,73]. With such a limited number of studies describing clinical effects, interpretation is limited.…”
Section: Clinical Studiesmentioning
confidence: 99%